The demographic and socio-economic characteristics of migrants, 1986-1996 - Punch, Aidan; Finneran, Catherine (Statistical and Social Inquiry Society of Ireland, 1999)
In the paper we draw on the following data sources: the censuses of 1986, 1991 and 1996 and the annual Labour Force Surveys (LFSs) for 1987 to 1997. Data from the annual series of population and migration releases are also used. This series was introduced in 1994 and covers the period since 1986. The paper commences with a consideration of some of the technical issues relating to the migration questions used in the above data sources. Section 3 deals with the stock of persons usually resident in this country who were either born abroad or who lived outside the country for a period of one year or more. The characteristics of the Irish-born and foreign-born persons who make up this group are compared with those of persons who never emigrated. To-date the only information published on the two categories of migrants is the basic demographic information published in the census reports. Section 4 examines the annual gross inflow data derivable from the censuses and labour force surveys while section 5 sets out the available information on the characteristics of the households from which persons have emigrated. The main findings of the paper are summarised in the final section and a number of topics for further study are suggested. - [p.2]
Read before the Society, 13 May 1999
Keywords: Demography - Ireland; Migration - Ireland; 314.15